Social and Economic Factors Influencing the Choice of Halal-Labeled Food and Beverages Among Muslim Generation Z: A Case Study of FEBI UINSU Students - Diva Anisyah Putri; Marliyah Marliyah; Imsar Imsar (JURNAL AT-TURAS, 2025)
This study explores how social and economic factors simultaneously influence the choice of halal-labeled food and beverages among Muslim Generation Z, with a particular focus on students of the Faculty of Islamic Economics and Business at the State Islamic University of North Sumatra. Previous research has largely examined these factors in isolation, leaving limited attention to their simultaneous effects in shaping halal consumption. Employing a quantitative survey of 100 respondents analyzed using confirmatory factor analysis (CFA), the study reveals that social factors, such as family and peer influence, serve as the strongest drivers of halal choices, while economic factors, including price and accessibility, function as moderating conditions. The findings contribute to the halal consumption literature by integrating social and economic dimensions within the context of Islamic higher education, thereby addressing a gap concerning young Muslim consumers. Practically, the study suggests that policymakers and halal certification bodies should enhance community-based halal literacy, while businesses may strengthen market engagement through price affordability strategies and the utilization of family and peer influence.